O teatro machadiano: Dom Casmurro e o texto teatral - Oliveira, Adriane Camara de (2014)
In this PhD Thesis we aim at developing a reading of Machado de Assis s theater in order to propose an interpretation of Dom Casmurro in two levels, in order to answer the question, which has prompted our research: to what extent the structure of the Dom Casmurro takes advantage of elements properly theatrical, that is, dramatic? We clarify that this question can only be formulated on the basis of a previous hypothesis: the central presence, in the composition of Dom Casmurro, often resorts to theatrical devices. Not only the narrator goes quite often to the theatre, and lives there relevant experiences, but also it is possible to identify a vocabulary properly theatrical throughout the text. That is, the theatre is both ambiance of the narrative and metaphor, which defines the relationship between characters, and theatre also determine Bento Santiago s worldview. The identification of the theatrical element as structure of the text of Dom Casmurro represents the contribution we aim at offering to the Machadian studies